Mesoscale fracture of a bearing steel: A discrete crack approach on static and quenching problems - Said Schicchi, Diego (2017)
A discontinuous approach aimed at modeling the brittle fracture behavior of mesoscopic 100Cr6 (SAE 52100) steel specimens is presented in this work. The proposal accounts for explicitly considering carbide particles and martensitic matrix in a metallographic image based mesoscale model. Two-dimensional numerical tests are carried out for the mesoscale specimens including a temperature dependent elastoplastic matrix dealing with the martensitic/austenitic phases and the embedded elastic carbide particles. A fracture damage-based interface constitutive rule is then employed for modeling the brittle behavior occurring at the joint between both the carbides-to-matrix and the matrix-to-matrix interfaces. The soundness and capability of the proposed formulation dealing with the quench cracking phenomenon is demonstrated. Experimental tensile test results on a 100Cr6 steel in its martensitic phase, at room and high temperature, are employed and the evaluation of microcracks formation during a High-Speed-Quenching test is also discussed.